2021
DOI: 10.1007/s11831-021-09634-2
|View full text |Cite
|
Sign up to set email alerts
|

Merits and Limitations of Mathematical Modeling and Computational Simulations in Mitigation of COVID-19 Pandemic: A Comprehensive Review

Abstract: Mathematical models have assisted in describing the transmission and propagation dynamics of various viral diseases like MERS, measles, SARS, and Influenza; while the advanced computational technique is utilized in the epidemiology of viral diseases to examine and estimate the influences of interventions and vaccinations. In March 2020, the World Health Organization (WHO) has declared the COVID-19 as a global pandemic and the rate of morbidity and mortality triggers unprecedented public health crises throughou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 141 publications
(161 reference statements)
0
16
0
Order By: Relevance
“…Effect of Cutting Speed and Weight % on Surface Roughness. The contour plot shown in Figure 12 indicates that the lowest roughness is obtained when weight % is high and cutting speed is low [31][32][33]. This area appears at the front right corner of the plot.…”
Section: Predicted Results By Taguchi Methodmentioning
confidence: 99%
See 1 more Smart Citation
“…Effect of Cutting Speed and Weight % on Surface Roughness. The contour plot shown in Figure 12 indicates that the lowest roughness is obtained when weight % is high and cutting speed is low [31][32][33]. This area appears at the front right corner of the plot.…”
Section: Predicted Results By Taguchi Methodmentioning
confidence: 99%
“…It was found that after 4 hr, nanoparticles start agglomerating. Hence, magnetic stirrer for 3 hr followed by an ultrasonication bath process for 2 hr was used to uniformly distribute and stabilize CuO nanoparticles [33][34][35][36]. The procedure followed in the preparation of nanofluid is well illustrated in Figure 2.…”
Section: Crystallite Sizementioning
confidence: 99%
“…Despite the extensive applicability of mathematical models across various disciplines, they exhibit notable limitations [ 221 , 222 ]. In biological applications, models often fail to capture the full complexity of biological systems, such as nonlinear interactions among multiple cells [ 223 ].…”
Section: Interdisciplinary Analysismentioning
confidence: 99%
“…Several previous studies have explored the potential of lifting NPIs as the vaccination coverage increased to a pre-set level via mathematical models ( 20–23 ). Many of these modeling studies have provided constructive suggestions on delaying the relaxation of NPIs, but the reliability of simulation evidence would be challenged by the uncertainty of real-world vaccine efficacy and the emergence of new variants ( 24 , 25 ). However, only one study has investigated the real-world combined effect of NPIs and vaccination and revealed a time-varying interaction effect between NPIs and vaccination ( 16 ).…”
Section: Introductionmentioning
confidence: 99%